Preservation of Escherichia coli M-17 Cells Immobilised in Gels Under Low Temperatures - Dorofeyeva, Tatyana V.; Kudokotseva, Elena V. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):187.